Urban mobility with a focus on gender: The case of a middle-income Latin American city - Olivieri, Cecilia; Fageda, Xavier (Journal of Transport Geography, 2021)
This study analyzes gender differences in travel patterns for the Metropolitan Area of Montevideo, Uruguay. By applying multilevel regression models, it provides estimates of the impact of individual and contextual factors on travel behavior. The paper's findings lend support to the household responsibility hypothesis, which claims that women's travel patterns are affected by the type of household in which they live and the consequent responsibilities or roles they assume. Furthermore, gender differences in travel patterns are reinforced across census tracts. The results indicate that policy makers need to consider gender differences when seeking to enhance urban planning decisions. © 2021 Elsevier Ltd
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; discipline; déplacements urbains; environnement; géographie; géographie urbaine; projet charge mentale; périodes historiques; régions géographiques; sciences humaines; thématiques; travail; uruguay